2020
DOI: 10.20511/pyr2020.v8n1.372
|View full text |Cite
|
Sign up to set email alerts
|

Problemas en el adolescente, mindfulness y rendimiento escolar en estudiantes de secundaria. Estudio preliminar

Abstract: ARTÍCULO DE INVESTIGACIÓN Problemas en el adolescente, mindfulness y rendimiento escolar en estudiantes de secundaria. Estudio preliminar Problems in Adolescents, Mindfulness and School Performance in High School Students. Preliminary Study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
1
2
0
2
Order By: Relevance
“…Regarding the effects of the intervention perceived by the participants, they were in line with those found in qualitative and quantitative studies, in which an increase in cognitive and emotional capacities has been reported [15,16,18,40,41]. There is evidence that an increase in participants' cognitive functions (e.g., level of attention) is associated with improved academic performance and overall performance in school activities [19][20][21][22]. Similarly, mindfulness training has enabled participants to improve their problem-solving skills in a variety of academic and relational contexts (e.g., with peers and friends), as they learned new strategies for coping with the difficulties that they face in their daily lives.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Regarding the effects of the intervention perceived by the participants, they were in line with those found in qualitative and quantitative studies, in which an increase in cognitive and emotional capacities has been reported [15,16,18,40,41]. There is evidence that an increase in participants' cognitive functions (e.g., level of attention) is associated with improved academic performance and overall performance in school activities [19][20][21][22]. Similarly, mindfulness training has enabled participants to improve their problem-solving skills in a variety of academic and relational contexts (e.g., with peers and friends), as they learned new strategies for coping with the difficulties that they face in their daily lives.…”
Section: Discussionsupporting
confidence: 77%
“…Black [18] claims that the repeated practice of centering one's attention strengthens neurocognitive capacity, especially within executive functions that have an impact on diverse areas of cognitive development associated with improved academic achievement and school performance [19][20][21][22]. For instance, Lawlor [23] emphasises the role of mindfulness in the development of competences that are central to social and emotional aspects of learning, such as self-management, self-awareness, and decision-making, amongst others.…”
Section: Introductionmentioning
confidence: 99%
“…El programa basado en Mindfulness ha mostrado una gran utilidad en la percepción de aumento de la relajación de los estudiantes participantes y, por lo tanto, una sensación de disminución del estrés, tal y como han señalado investigaciones previas (Van de Weijer-Bergsma, et al, 2012;Kuyken, et al, 2013;Amutio-Kareaga, et al, 2015;Mercader, 2020). Se ha evidenciado una contribución positiva reduciendo los niveles de ansiedad y mejorando la atención y concentración, tal y como reseñan estudios previos (Franco, et al, 2010;Zoogman, et al, 2014;Langer, et al, 2015).…”
Section: Discussionunclassified
“…En este sentido, Hölzet, et al (2011) sugieren que existe una relación intrínseca entre el Mindfulness y la gestión emocional, y que este conjunto de técnicas es capaz de producir transformaciones en uno mismo. Asimismo, Mercader (2020) ha evidenciado en adolescentes una cierta correlación entre la capacidad de ser consciente en el momento presente y la disminución de variables como la ansiedad, la depresión, los problemas interpersonales, la incertidumbre sobre el futuro y el riesgo psicosocial. Con anterioridad, Vargas (2010) y Langer, et al (2015) también lo habían mencionado, valorando el efecto positivo del Mindfulness incluso sobre variables fisiológicas, como la regulación de la presión sanguínea o el sistema inmunitario.…”
Section: Introductionunclassified
“…From another perspective, the practice of mindfulness has spread rapidly among the world's adult population in recent years, following its proven effectiveness in regulating emotions and optimizing cognitive patterns. The number of studies and research on this practice and analysis of its efficacy with children and adolescents has been increasing due to its demonstrated effectiveness in improving more ecosocial behaviors, enhancing general wellbeing [17,18], improving psychological symptoms [19], and faster information processing. In the educational context, its practice has demonstrated effectiveness in cognitive performance and significant relationships in measures of stress, coping, and resilience [20].…”
Section: Introductionmentioning
confidence: 99%